Building a Digital Innovation Ecosystem through Knowledge Sharing and a Conducive Business Climate - Sarman, Rohmat; Affandi, Azhar; Djulius, Horas; Priadana, Sidik (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: This research investigates the role of knowledge sharing and a supportive business climate in establishing a digital innovation ecosystem for Muslim entrepreneurs in West Java.Methodology: The study utilized a quantitative approach, combining descriptive and verification methods through an explanatory survey to gather data from 400 entrepreneurs. A proportional cluster random sampling method was employed, using business type as the basis for stratification. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS version 3.2.9.Finding: The results indicate that: 1) Knowledge sharing has a positive and significant impact on the business climate. 2) Knowledge sharing positively and significantly influences digital innovation. 3) The business climate has a positive and significant effect on digital innovation. 4) Furthermore, the business climate mediates the relationship between knowledge sharing and digital innovation.Conclusion: The research concludes that knowledge sharing is vital in improving both the business climate and digital innovation among Nahdliyin entrepreneurs in West Java. The significant and positive influence of knowledge sharing on the business climate highlights its role in creating a supportive entrepreneurial environment. Additionally, the business climate directly affects digital innovation and mediates the relationship between knowledge sharing and digital innovation. These insights suggest that enhancing digital innovation among entrepreneurs should involve fostering knowledge sharing and developing a conducive business climate. The study emphasizes the need to integrate these elements to build a strong digital innovation ecosystem that can improve entrepreneurial performance.